Analysis of the readability of patient education materials from surgical subspecialties. (26th June 2013) - Hansberry, David R.; Agarwal, Nitin; Shah, Ravi; Schmitt, Paul J.; Baredes, Soly; Setzen, Michael; Carmel, Peter W.; Prestigiacomo, Charles J.; Liu, James K.; Eloy, Jean Anderson
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Patients are increasingly using the Internet as a source of information on medical conditions. Because the average American adult reads at a 7th‐ to 8th‐grade level, the National Institutes of Health recommend that patient education material be written between a 4th‐ and 6th‐grade level. In this study, we assess and compare the readability of patient education materials on major surgical subspecialty Web sites relative to otolaryngology. Study Design Descriptive and correlational design. Methods Patient education materials from 14 major surgical subspecialty Web sites (American Society of Colon and Rectal Surgeons, American Association of Endocrine Surgeons, American Society of General Surgeons, American Society for Metabolic and Bariatric Surgery, American Association of Neurological Surgeons, American Congress of Obstetricians and Gynecologists, American Academy of Ophthalmology, American Academy of Orthopedic Surgeons, American Academy of Otolaryngology–Head and Neck Surgery, American Pediatric Surgical Association, American Society of Plastic Surgeons, Society for Thoracic Surgeons, and American Urological Association) were downloaded and assessed for their level of readability using 10 widely accepted readability scales. Results The readability level of patient education material from all surgical subspecialties was uniformly too high. Average readability levels across all subspecialties ranged from the 10th‐ to 15th‐grade level. Conclusions Otolaryngology and other surgical subspecialties Web sites have patient education material written at an education level that the average American may not be able to understand. To reach a broader population of patients, it might be necessary to rewrite patient education material at a more appropriate level. Level of Evidence N/A. Laryngoscope, 124:405–412, 2014